The Portrayal of Women in Popular Punjabi Music. Issue 1 (10th March 2022) - Nancy,
Abstract: The Punjabi music industry, which generates an annual revenue of around ₹7 billion, is the largest independent music industry in India. Popular Punjabi songs produced for entertainment are also ideological constructs. They represent, reproduce, and reinforce gender disparities and foster the internalization of longstanding male hegemonic cultural beliefs. This article studies the lyrics and visual imagery of 10 popular Punjabi songs. The analysis of selected songs offers significant insights into gender power relations and identity construction in a patriarchal Punjabi society.